The Two Faces of Russia Foreign Policy toward China and Taiwan (Global Focus, 2021)
Russia, as one of the key actors in international politics, faces problematic issues in Chinese-Taiwan Relations. As a significant player, Russia reserves a close and stable relationship with China. However, Russia could not avoid Taiwan's significant role in Northeast Asia, especially its role in allying with the West. Taiwan undoubtedly offers a promising prospect for the Russian economy, but political relations with Taiwan could not significantly contribute to Russian FP. In this paper, Russian foreign policy will be examined on both sides, Russian foreign policy toward China and Russian foreign policy toward Taiwan. The purposes of this paper are trying to analyze the Russian foreign policy dilemma toward China-Taiwan relation. The analysis of this paper will focus on President Vladimir Putin as the decision-maker and explore all circumstances that will influence the decision-making process. The level of analysis implemented in this paper is domestic politics that significantly contribute to Russian foreign policy decision-making. This paper will gather secondary data from the news, journal, and book as the primary sources. The paper's outcome is analyzing Russian foreign policy's dilemma and exploring how Russian foreign policy toward current dynamics of China-Taiwan Relations.